El marketing digital en las pequeñas y medianas empresas (PYMES) del Sector Financiero del cantón Latacunga. - Paredes Paredes, Daniela Estefani (2017)
The present study investigated, "Digital marketing in small and medium-sized enterprises (SMEs) of the financial sector of the canton of Latacunga, establishing a prior structure of knowledge to identify relevant spaces where they can interact in a positive manner but, as the study was channeled this could not be fulfilled, due to the limitations that existed in the object universe, such as the theoretical ones that are established because there are not enough sources of information to deal with the subject. Also, due to the complications of access to the facilities of small and medium-sized companies, since in many of these they have the privilege of reserving their information. It is important in this section to mention that informative sources such as books, articles or internet sites were insufficient to continue with the development of research on SMEs, therefore, the object of study was done to credit unions of which 6 institutions were chosen, for the openness and ease of accessing their information within marketing and how they apply it. The methodology used for the development of the research was inductive because since this part of something particular topic to get the conclusions, as in the case of research began with the study of SMEs and their classification for later reach the savings and credit cooperatives, the quantitative approach was also used, which helped to obtain the necessary information, using the technique of the survey, applied to the partners and legal representatives of 6 savings and credit cooperatives in the financial sector of Latacunga, where the results obtained that the study population, was that they do not take advantage of 100% the digital marketing and the management of their propaganda, to publicize all the service, the growth and confidence to their clients, as a base fundamental of the financial system in addition, to stay at the forefront in the dissemination of their services they provide. We must add that cooperatives must take the reins of certain niche markets where people are really exploring how is the web. With the support through the theoretical framework as a fundamental pillar of the research, it constitutes the base where the development of the degree work that can be constituted was supported, selecting the sector of savings and credit cooperatives of Latacunga, for being one of the sectors where information could be collected to be more feasible, also because there is access to data search. The result of the study was the relationship between digital marketing and the increase in the number of members, which in turn generates an increase in loans, because companies using digital information and communication tools are a new niche. of market where, the cooperatives are made known and increase the number of partners thus establishing more income for them. The organizations that use digital marketing are 33.34%, the percentage of use is low, they are not using it 100%, most cooperatives do not use any tool, the entities have a weakness in the use of social networks in those that are more people to be able to promote themselves. Companies wishing to use digital marketing will be able to promote their services or products offered in the market, obtaining an acceptance to improve their sales, helping to retain and attract customers, in the future to become more competitive by exploring new niches of market.